2010
DOI: 10.1007/s00198-010-1484-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of serum 25-hydroxyvitamin D levels in adult patients with inflammatory bowel disease

Abstract: SummaryPatients with inflammatory bowel disease (IBD) are at risk of osteoporosis. Vitamin D (vitD) deficiency is known as a risk factor of osteoporosis. We observed low vitD blood levels in adult IBD patients both at the end of summer and winter. Furthermore, effects of oral vitD supplementation in (generally low) daily dosages were poor.IntroductionPatients with IBD are at risk of osteoporosis. This study evaluates seasonal vitD status, determinants of vitD deficiency and effects of vitD supplementation in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 42 publications
(42 reference statements)
2
32
1
3
Order By: Relevance
“…The finding of low levels of vitamin D in IBD patients is common (9,22), and from our study, most of our IBD patients have inadequate levels of vitamin D and about a fifth were vitamin D deficient. As mentioned previously, Malaysia is a tropical country with high temperatures all year round without the seasonal variation in temperate climates (23). Despite the large amount of sunlight, however, an inadequate vitamin D level is generally a common phenomenon in Malaysia, even in the general population, particularly in urban areas (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of low levels of vitamin D in IBD patients is common (9,22), and from our study, most of our IBD patients have inadequate levels of vitamin D and about a fifth were vitamin D deficient. As mentioned previously, Malaysia is a tropical country with high temperatures all year round without the seasonal variation in temperate climates (23). Despite the large amount of sunlight, however, an inadequate vitamin D level is generally a common phenomenon in Malaysia, even in the general population, particularly in urban areas (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible risk factors such as age (8,9), low body mass index (BMI) (8,10), malabsorption, vitamin D and calcium defi ciencies (11,12), bowel resection (9,13), hypogonadism, corticosteroid treatment (9,12,13,14,15), smoking (16), reduced physical activity and genetic factors (17).…”
mentioning
confidence: 99%
“…Although there is evidence that long-term corticosteroid therapy reduces the BMD (9,12,13,14,15,22,23,24), some of stud-ies have suggested that BMD in IBD is unrelated to corticosteroid use (25,26,27,28,29). Considering the fact that newly diagnosed patients already have a reduced bone mineral density (BMD), there is a strong case for suggesting that demineralization in patients with IBD occurs primarily as a consequence of intestinal infl ammation.…”
mentioning
confidence: 99%
“…A major and common problem in patients with IBD is vitamin D deficiency. In a study by Bours et al, which included 316 patients, vitamin D deficiency was present in 39% of the patients during summer and 57% of the patients during winter [11]. Indications for DEXA testing according to the British Society of Gastroenterology may be: persistent active inflammatory bowel disease, > 10% weight loss, BMI of < 20 kg/m 2 , age > 70 years of age, treatment with GCs for a period of six months, patients < 65 years of age, in whom treatment with glucocorticoids is planned, if there are other known risk factors for osteoporosis.…”
Section: Non-specific Inflammatory Bowel Diseases and Osteoporosismentioning
confidence: 99%